Comparative Study Between Traditional Grammar and Modern Linguistics - Jamoldinov Sanjarbek (Genius Journals, 2022)
This article analysis the traditional grammar and modern linguistics, and mainly reveals their similarities and differences. It is clear that linguistics is a science of linguistic study, which starts from descriptive grammar, structure grammar, functional grammar, transformational-generative grammar and many other grammars. It points out that though they are quite different, traditional grammar is the base from which modern linguistics is derived
Keywords: Traditional Grammar; Modern Linguistics; Descriptive Grammar; Language